2017
DOI: 10.1111/jasp.12485
|View full text |Cite
|
Sign up to set email alerts
|

Imagined contact in high conflict settings: The role of ethnic group identification and the perspective of minority group members

Abstract: Recent contact literature has shown that imagining a positive intergroup encounter improves intergroup attitudes and behaviors, yet less is known about the effects of imagined contact in high conflict settings. We conducted three studies to understand the potential effects of imagined intergroup contact among ethnic Turks (majority status) and ethnic Kurds (minority status) in the Turkish-Kurdish interethnic conflict setting. Study 1 (N 5 47, Turkish) tested standard imagined contact effects (neutral vs. stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 76 publications
2
25
1
Order By: Relevance
“…Moreover, compared to majority group members for whom intergroup anxiety stems from being accused as prejudiced, minority group members’ intergroup anxiety often stems from their negative expectations from the majority group (Devine & Vasquez, ; Tropp, Hawi, et al ., ; Tropp, Mazziotta, et al ., ), which suggests that for the minority group in particular, the perception of the majority group's attitudes towards the minority group may be an immediate consequence of intergroup contact. In line with this, previous studies demonstrated that positive contact experiences could improve minorities’ perception of majority group's attitudes and beliefs (Bagci, Piyale, & Ebcim, ; Tropp, Hawi, et al ., ; Tropp, Mazziotta, et al ., ) and such expectancies from the outgroup are likely to shape own outgroup attitudes (e.g., López‐Rodríguez, Zagefka, Navas, & Cuadrado, ; Zagefka et al ., ).…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…Moreover, compared to majority group members for whom intergroup anxiety stems from being accused as prejudiced, minority group members’ intergroup anxiety often stems from their negative expectations from the majority group (Devine & Vasquez, ; Tropp, Hawi, et al ., ; Tropp, Mazziotta, et al ., ), which suggests that for the minority group in particular, the perception of the majority group's attitudes towards the minority group may be an immediate consequence of intergroup contact. In line with this, previous studies demonstrated that positive contact experiences could improve minorities’ perception of majority group's attitudes and beliefs (Bagci, Piyale, & Ebcim, ; Tropp, Hawi, et al ., ; Tropp, Mazziotta, et al ., ) and such expectancies from the outgroup are likely to shape own outgroup attitudes (e.g., López‐Rodríguez, Zagefka, Navas, & Cuadrado, ; Zagefka et al ., ).…”
Section: Introductionsupporting
confidence: 77%
“…In line with our expectations, we found cross‐group friendships to be related to more positive majority outgroup attitudes and relate to higher levels of collective self‐esteem, that is, the extent to which disabled people feel socially accepted. Previous research has demonstrated that contact strategies may be even more effective in changing minority group members’ perceived outgroup attitudes from the majority, than changing their own attitudes (Bagci, Piyale, & Ebcim, ). Therefore, for minority groups, intergroup contact may have a more prominent role in changing how minority group members feel about themselves and how they perceive themselves from the perspective of the majority group.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have examined the effects of imagined contact among minority groups, and even fewer have compared the effects in majority and minority groups. These few studies have shown that the positive effects of imagined contact on outgroup attitudes are demonstrated among majority group members, but not among minority members, in Mexico (Stathi & Crisp, 2008) and in Turkey (Bagci, Stathi, & Piyale, 2019) or have an impact among minority Kurd members on certain measures, not including outgroup attitudes (Bagci, Piyale, & Ebcim, 2018). It has also been found that although imagined contact had positive outcomes among Eastern European minority members in the United Kingdom; minority Kurd members in Turkey, especially those who were more identified with their ingroup, did not reveal positive effects following imagined contact (Bagci et al, 2019).…”
Section: Prejudice Toward Strongly Identified Outgroup Membersmentioning
confidence: 99%
“…Although research has demonstrated the benefits of imagined contact as regards improved intergroup relationships, imagined contact has been rarely applied among minority group members (but see Bagci, Piyale, & Ebcim, 2018;Bagci, Stathi, & Piyale, in press;Stathi & Crisp, 2008) and no research to date has examined specifically whether imagined contact may produce the suggested unintended consequences of direct contact, i.e., reduced motivation to act collectively on behalf of the ingroup (e.g., Dixon et al, 2010). To our knowledge, the only two studies examining the role of imagined contact on variables related to collective action investigated whether imagined contact increased advantaged group members' support for disadvantaged group members' rights (see Bagci et al, 2018;Carvalho-Freitas & Stathi, 2017).…”
Section: Imagined Intergroup Contact Theorymentioning
confidence: 99%